2019
DOI: 10.1242/jcs.228940
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Fhl2 leads to delayed neuronal cell migration and premature astrocyte differentiation

Abstract: The four and a half LIM domains protein 2 (Fhl2) is an adaptor protein capable of mediating protein-protein interactions. Here, we report for the first time phenotypic changes in the brain of Fhl2-deficient mice. We showed that Fhl2 is expressed in neural stem cells, precursors and mature cells of neuronal lineage. Moreover, Fhl2 deficiency leads to delayed neuroblast migration in vivo, premature astroglial differentiation of neural stem cells (NSCs) in vitro, and a gliosis-like accumulation of glial fibrillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
8
1
Order By: Relevance
“…Wei et al reported that Ptgds accumulation in Cul4b knockout mice led to an increase in glial fibrillary acidic protein (GFAP) (Zhao et al, 2015). Furthermore, Soung demonstrated that Fhl2 deficiency resulted in an accumulation of GFAP + astrocytes, and led to the disturbed arrangement and delayed migration of neuroblasts and the development of neural stem cells (Kim et al, 2019). Based on these studies, we speculate that Ptgds‐induced GFAP accumulation may play a vital role in neuronal migration.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al reported that Ptgds accumulation in Cul4b knockout mice led to an increase in glial fibrillary acidic protein (GFAP) (Zhao et al, 2015). Furthermore, Soung demonstrated that Fhl2 deficiency resulted in an accumulation of GFAP + astrocytes, and led to the disturbed arrangement and delayed migration of neuroblasts and the development of neural stem cells (Kim et al, 2019). Based on these studies, we speculate that Ptgds‐induced GFAP accumulation may play a vital role in neuronal migration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FHL2-KO mice seem to have a reduced threshold for development of several chronic diseases. It was reported that loss of the LIM-only protein FHL2 encouraged the development of corneal angiogenesis, hypertrophic cardiomyopathy (38), osteopenia (37), fibrosis (25,39,40), arthritis (30,31), psoriasis (30), and gliosis in the adult brain (41).…”
Section: Expression Of Fhl2 During Wound Healingmentioning
confidence: 99%
“…To evaluate the physiological role of FHL2 in adult-born DGCs, we constructed inducible overexpression and knockdown of FHL2 vectors packaged into retroviruses (Figures 3D,E). In order to avoid potential effects on cell fate determination (Kim et al, 2019), we induced expression with doxycycline from day 3, as shown in Figures 3D,E. We observed that all FHL2-RFP positive cells expressed Prox1 and DCX ( Figure 3F) thus validating our experimental approach to target adult-born neurons without affecting cell fate choice.…”
Section: Expression and Genetic Manipulation Of Fhl2 In Adult-born Dgcsmentioning
confidence: 58%
“…Although several studies have shed light on the relevance of FHL2 in terms of CNS-related pathology, including epilepsy and glioblastoma (Jamali et al, 2006;Kleiber et al, 2007;Li et al, 2008;Okamoto et al, 2013), the understanding of the regulatory role of FHL2 is yet to be fully appreciated. Recently, Kim et al (2019) reported that FHL2 is expressed by NSCs and plays a role in both fate determination of cells as well as the migratory capabilities of their progeny cells (Kim et al, 2019). To assess the physiological implication of FHL2 on the dynamic process of dendritic arborization, we report for the first time that FHL2 is expressed endogenously in adult-born hippocampal neurons and interestingly that there is a significant decline in its expression observed as these neurons mature, suggesting the participation of FHL2 during the early development of adult-born neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation